Weaving Mat(h)s - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2014)
This column is a forum for discussion of mathematical communities throughout the world, and through all time. Our definition of ‘‘mathematical community’’ is the broadest: ‘‘schools’’ of mathematics, circles of correrspondence, mathematical societies, student organizations, extra-curricular educational activities (math camps, math museums, math clubs), and more. What we say about the communities is just as unrestricted. We welcome contributions from mathematicians of all kinds and in all places, and also from scientists, historians, anthropologists, and others.